2013
DOI: 10.1001/jamapediatrics.2013.2534
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Increased Coverage of Participatory Women’s Groups on Neonatal Mortality in Bangladesh

Abstract: isrctn.org Identifier: ISRCTN01805825.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 18 publications
(41 reference statements)
5
141
1
3
Order By: Relevance
“…Many health problems related to pregnancy are preventable, detectable, or treatable by trained health workers (Carroli, Rooney, & Villar, 2001;WHO, 1994). In addition, researchers showed that ANC visits during pregnancy have positive impact on postnatal utilization of health services which have a positive impact on the health status of the child (Dhakal et al, 2007;Oyerinde, 2013) including a reduction in neonatal deaths (Fottrell et al, 2013).…”
mentioning
confidence: 99%
“…Many health problems related to pregnancy are preventable, detectable, or treatable by trained health workers (Carroli, Rooney, & Villar, 2001;WHO, 1994). In addition, researchers showed that ANC visits during pregnancy have positive impact on postnatal utilization of health services which have a positive impact on the health status of the child (Dhakal et al, 2007;Oyerinde, 2013) including a reduction in neonatal deaths (Fottrell et al, 2013).…”
mentioning
confidence: 99%
“…The study in Bangladesh (Fottrell et al, 2013) also showed that increased early initiation of breastfeeding (within one hour of birth) was significantly different (p<0·05) between intervention and control groups in published data.…”
Section: Journal Of Advanced Academic Research (Jaar)mentioning
confidence: 90%
“…In a separate regression model (model 2), results were also adjusted for the difference in mother-child height z-score to understand whether any of the anthropometric differences observed at 24–48 months could be explained by a PWG intervention survival effect at birth 9. Underlying this is the assumption that observed intervention effects on neonatal mortality resulted in the survival of children with lower birth weights,14 and that in the absence of this survival effect, the mean mother-child height difference would be similar in the study arms.…”
Section: Methodsmentioning
confidence: 99%
“…One such PWG intervention, originally delivered in rural Bangladesh in 2009–2011 as part of a cluster randomised controlled trial, covered approximately 46 000 reproductive-age women (15–49 years) during preconception, pregnancy and the postpartum period. The intervention showed a 38% reduction in neonatal mortality, and improved hygienic delivery and essential newborn care practices 9. It used a participatory learning and action (PLA) cycle of monthly meetings facilitated by lay women.…”
Section: Introductionmentioning
confidence: 99%